2010
DOI: 10.1007/s00167-010-1274-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of degenerative medial meniscus extrusion: radial component and knee osteoarthritis

Abstract: meniscal extrusion was greater and more severe in knees with a radial tear component than in knees without a radial component. The incidence and degree of major extrusion was similar in knees with root tears and non-root tears. A radial component and knee osteoarthritis severity were similarly predictive of absolute and relative extrusion. Meniscal extrusion in osteoarthritic knees was associated not only with degenerative meniscal tear but also with osteoarthritis severity. Therefore, arthroscopic meniscal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
120
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 28 publications
6
120
1
Order By: Relevance
“…We demonstrated that meniscal tears are not the only factors associated with meniscal extrusion; other factors, such as tibiofemoral cartilage damage and knee malalignment, are independently associated with meniscal extrusion. The relationship between meniscal tears and meniscal extrusion has been explored previously (22)(23)(24)(25)(26)30). The intricately woven pattern of collagen fibrils is responsible for the strength of the meniscus, which maintains its shape and structure when axially loaded (43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We demonstrated that meniscal tears are not the only factors associated with meniscal extrusion; other factors, such as tibiofemoral cartilage damage and knee malalignment, are independently associated with meniscal extrusion. The relationship between meniscal tears and meniscal extrusion has been explored previously (22)(23)(24)(25)(26)30). The intricately woven pattern of collagen fibrils is responsible for the strength of the meniscus, which maintains its shape and structure when axially loaded (43).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (24) assessed the association of arthroscopy-depicted chondral lesions and preoperative radiographic KellgrenLawrence grade with meniscal extrusion and found that only the Kellgren-Lawrence grade was significantly related to extrusion. However, a cross-sectional MR imaging study conducted by Lerer et al (25) showed a significant association between moderate to severe MR imaging-depicted medial compartment articular cartilage damage and medial meniscal extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 It has also been reported that extrusion of the meniscus is associated with development of osteoarthritis (OA) 5,6 and knee pain 7 in patients with OA. The posterior root tear or radial tear could be surgically repaired to the normal shape; however, meniscal transplantation has been the only surgical intervention for the extrusion of the lateral meniscus after meniscectomy or in patients with OA.…”
mentioning
confidence: 99%